Pembuatan mesin uji tarik kapasitas kecil: bagian data akuisisi - Pandiatmi, Pandri; Okariawan, IDK; Sulistyowati, Emmy Dyah; Salman, S.; Adhi, IG.A.K. Chatur (Universitas Mataram, 2017)
For the purposes of practicum and student research in the field of materials, tensile test equipment is very important. But the test equipment that is in the Department of Mechanical Engineering, University of Mataram has a very large capacity so it is not suitable for testing materials such as plastics and composites so this study bertujuann to make small capacity tensile testing machine for purposes of practicum and student research in the field of polymer materials and composites. Due to limited funds, the research is focused on making data acquisition tensile testing machine. Necessary materials are on site, cable, lead solder, lacquers cable socket and supported by laboratory equipment mechanical engineering majors who have been there, but some of the components to be purchased as load cell, electronic extensometer, and the operational amplifier module arduino uno boad. Design data acquisition consists of a sensor that is load cell, extensometer electronic, signal conditioning is an operational amplifier that is arduino uno data recording boad connected with the personal computer and data processing using LabView software so that the output of the data acquisition is in the form of tables and graphs. With their small capacity tensile testing machine is expected to provide an additional means of learning in the laboratory and student research.